Desmoplastic small round cell tumor of the parotid gland-report of a rare case and a review of the literature - Kanako C. Hatanaka; Emi Takakuwa; Yutaka Hatanaka; Akira Suzuki; Satoshi IIzuka; Nayuta Tsushima; Tomoko Mitsuhashi; Shintaro Sugita; Akihiro Homma; Shojiroh Morinaga; Tadashi Hashegawa; Yoshihiro Matsuno (BMC, 2019)
Abstract Background Desmoplastic small round cell tumor (DSRCT) is a rare soft tissue tumor that generally involves the retroperitoneum, pelvis, omentum and mesentery in younger patients. However, extra-abdominal DSRCT is very rare. Case presentation A 49-year-old Japanese man noticed a mass in the right parotid gland. Ultrasound examination revealed a solid tumor about 2 cm in diameter. Computed tomography (CT) of the whole body revealed no other tumors or lymph node swelling. Superficial parotidectomy was performed. Histologically, the tumor was composed of various-sized tumor cell nests in an abundant fibromyxoid and collagenous background. The tumor cells were small to medium-sized. Immunohistochemistry showed that the tumor cells were immunoreactive for epithelial markers and desmin. They also showed strong nuclear staining with a Wilms tumor 1 (WT1) antibody detecting the C-terminal region (C-WT1), but not the N-terminal region (N-WT1). We also performed 3'/5' expression imbalance assay based on reverse transcription polymerase chain reaction (RT-PCR) to determine whether aberrant WT1 gene expression was present. This tumor was found to lack 5'-regional expression of the WT1 gene, as well as immunoreactivity with the N-WT1 antibody. Finally, fluorescence in situ hybridization (FISH) and RT-PCR analyses revealed the presence of a gene showing fusion between exon 7 of EWSR1 and exon 8 of WT1. The tumor was diagnosed as a DSRCT of the right parotid gland. The patient has been followed for 3 years without recurrence or metastasis. Conclusions Although DSRCT in the salivary gland is extremely rare, it should be included in the differential diagnosis of poorly differentiated salivary gland neoplasms, especially with a fibromyxoid background. Pathologists should bear in mind that DSRCT may occur in major salivary glands and should perform immunohistochemistry with appropriate antibodies, not only those against keratin and desmin, but also one detecting the C-terminal region of WT-1. Furthermore, molecular detection of EWSR1-WT1 fusion gene conclusively confirmed the diagnosis of DSRCT in this uncommon location.